OBSERVATIONS OF THE MUTUAL PHENOMENA OF THE GALILEAN MOONS IN 2009 - Koshkin, N.; Korobeynikova, E.; Shakun, L.; Dorokhov, N.; Doan, D. L.; Manh, T. N.; Minh, T. N.; Udovichenko, S.; Bondarenko, Y.; Kashuba, V.; Klabukova, A. (Одеські астрономічні публікації, 2009)
The instrumental and ephemeris preparation for the photometric observations of the mutual phenomena in the system of planetary satellites was conducted within the PHEMU09 project. Several reliable light curves and more than two tens of preparatory photometric observations of various mutual phenomena in the Jovian system were obtained. The observation data were processed, and the moments of the greatest phases of the phenomena were defined. The difference of moments of the observed greatest phases of the phenomena and the ephemerides, computed by the theory of V. Lainey, is about 0.02÷0.5 minutes. To construct an improved theory of motion of the Jovian moons, the observations are to be used for the concluding processing in the IMCCE (Institute de Mecanique et de calcul des ephemerides, France) that coordinates the PHEMU09 campaign.